Clinical surveillance and PSA outcomes among patients with non-metastatic castration resistant prostate cancer (nmCRPC) treated with a next-generation androgen receptor inhibitor (ARI) in urology clinics with or without in-office dispensing (IOD). Issue 28 (1st October 2022) - Burbage, Sabree; Waters, Dexter; Rossi, Carmine; Kinkead, Frederic; Pilon, Dominic; Muser, Erik; Ellis, Lorie
Abstract : 410 Background: As use of oral therapies in prostate cancer treatment increases, IOD of oral medication has become more common. The objective of this study was to describe clinical surveillance practices and PSA outcomes in nmCRPC patients (pts) treated in clinics with or without IOD. Methods: nmCRPC pts with ≥1 ARI prescription (Rx) were identified in data from 95 US urology practices between 2018-2021. Pts were categorized into 3 groups: (1) Treated in IOD clinic and received ARI onsite within 14 days of Rx (IOD+), (2) Treated in IOD clinic but no onsite ARI receipt within 14 days of Rx (IOD-), and (3) Treated in a clinic without IOD (non-IOD). Descriptive analyses were conducted on pt characteristics, PSA and imaging data. PSA response, reported using Kaplan-Meier rates, was defined as ≥50% reduction in post-index (PI; index date = 14 days after 1 st ARI Rx) PSA compared to baseline PSA (measured within 13 weeks before 1 st ARI prescription). PSA progression was defined as ≥25% increase in PI PSA above baseline PSA. Results: 3, 300 nmCRPC pts were identified (N = 615 IOD+; 2, 474 IOD-; 211 non-IOD). Baseline characteristics differed for race, use of bone resorption agents and 1 st generation anti-androgens, and PSA doubling time (PSADT; table). By 6 months PI, PSA screening was observed in similar proportions of pts in IOD and non-IOD, while PSA response was observed in a higher proportion of IOD+ (80%) than IOD- (64%) or non-IOD (63%). PSA progression was observed in fewer IOD+ pts (10%) than IOD- (16%) or non-IOD (17%). PI imaging was conducted in similar proportions of pts in IOD and non-IOD clinics; however, non-IOD performed more imaging per pt and time to imaging was shorter than in IOD+ clinics. Conclusions: Differences were noted in patient characteristics and prior medication use in ARI-treated patients within IOD and non-IOD clinics. IOD+ was observed to have higher rates of PSA response, fewer patients with PSA progression, and use fewer imaging tests after ARI initiation than non-IOD or IOD-. Additional studies controlling for differences in baseline characteristics and examining longer term outcomes are needed to understand how IOD services impact quality of patient care. IOD+ (n = 615) IOD- (n = 2, 474) Non-IOD (n = 211) White race, n (%) 416 (67.6) 1, 690 (68.3) 169 (80.1) Prior 1 st generation antiandrogen, n (%) 100 (16.3) 393 (15.9) 51 (24.2) Bone antiresorptive therapy, n (%) 147 (23.9) 519 (21.0) 24 (11.4) PSADT ≤10 mos, n (%) 161 (73.2) 509 (69.8) 46 (80.7) PSA test every 6 mos, n (%) 467 (75.9) 1, 701 (68.8) 150 (71.1) PSA50 Response, KM rate % [95% CI] 80.0 [76.2, 83.6] 63.8 [61.6, 66.0] 62.5 [55.1, 70.0] Pts with ≥1 CT scan, n (%) 164 (26.7) 640 (25.9) 53 (25.1) CT scans, mean ± SD 4.6 ± 12.7 4.7 ± 11.5 8.0 ± 16.5 Days from index to most recent CT scan, mean ± SD 310.3 ± 265.8 274.2 ± 247.4 277.3 ± 237.3